Gestão de serviços em bibliotecas: melhoria com foco no cliente Service management in libraries: improvement with focus on the customer p.198-218 - Silva, Chirley Cristiane Mineiro da; Rados, Gregório Jean Varvakis (Revista ACB, 2005)
Realiza de forma sucinta um estudo de caso sobre os serviços em bibliotecas. Busca alternativas para viabilizar indicadores que demonstrem as principais dificuldades e necessidades dos usuários em relação aos serviços prestados pelas bibliotecas. Tem como objetivo identificar as características dos serviços em bibliotecas decorrentes dos impactos das novas tecnologias e mapear a melhoria da qualidade dos serviços. O método utilizado foi entrevista a usuários de determinada biblioteca, identificando a qualidade desejada e a qualidade observada nos serviços. Com base nos resultados, foram traçados indicadores para as melhorias nos serviços e realizado uma análise da influência da tecnologia. Assim, a pesquisa procurou identificar indicadores para possibilitar e melhorar os serviços em bibliotecas, dando ênfase ao cliente. Abstract: It carries through of form sucinta a case study on the services in libraries. Search alternative to make possible pointers that demonstrate to the main difficulties and necessities of the users in relation to the services given for the libraries. It has as objective to identify the characteristics of the services in decurrent libraries of the impacts of the new technologies and to mapear the improvement of the quality of the services. The used method was interview the users of determined library, identifying the desired quality and the quality observed in the services. On the basis of the results, had been indicating tracings for the improvements in the services and carried through an analysis of the influence of the technology. Thus, the research looked for to identify pointers to make possible and to improve the services in libraries, giving emphasis to the customer. Keywords: Service Management; Library services - manangement, Library